Trends on Integrating Technologies for Mobile and Personalized Care - Bricon-Souf, N.; Jaulent, M.-C. (Yearbook of Medical Informatics, 2013)
Objectives: Summarize current excellent research and trends in the field of Health and Clinical Management.Method: Synopsis of the articles selected for the IMIA Yearbook 2013.Results: Five papers from international peer-reviewed journals have been selected for the section of Health and Clinical Management.Conclusions: The selected articles illustrate current research regarding the Health and Clinical Management and showed that it is impacted by the importance of personalizing the care and integrating the use of mobile and connected technologies.
Keywords: Health and clinical management; patient care management; medical record systems; technologies in healthcare; telemedicine